2017
DOI: 10.21625/essd.v2i1.86
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental and Economical Impacts of Using Media Façades in Commercial Buildings in Egypt

Abstract: Media façades is a subdivision of urban computing integrating digital displays into buildings, including structures and road furniture. It is frequently connected with over dimensional screens and vivified, lit up publicizing, and places like Times Square. The façade is dematerialized and transformed into one immense promoting medium for sending messages. Media façades can bring out the most assorted feelings, from a major city feeling to disturbance at light contamination. They are likewise seen as Pop Art or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Sustainability: The sustainability of media facade examples was examined under the topics of material selection and energy generation. Moreover, samples from the control group indicated that material use was common for ensuring sustainability, and the number of practices aiming to generate energy was quite limited, which supports the results achieved by other studies from the relevant literature (Abdou et al, 2017). However, regarding the examples in Turkey, approaches to sustainability were at a lower degree compared to other samples from the control group (Figure 16).…”
Section: Evaluation Of Media Facades Samples and Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Sustainability: The sustainability of media facade examples was examined under the topics of material selection and energy generation. Moreover, samples from the control group indicated that material use was common for ensuring sustainability, and the number of practices aiming to generate energy was quite limited, which supports the results achieved by other studies from the relevant literature (Abdou et al, 2017). However, regarding the examples in Turkey, approaches to sustainability were at a lower degree compared to other samples from the control group (Figure 16).…”
Section: Evaluation Of Media Facades Samples and Resultssupporting
confidence: 78%
“…The use of the illumination with daylight in media facade designs as a homogeneous source of light in indoor areas as a result of certain procedures should be considered as a passive designing parameter. Forming dynamic elements, generation of double skin elements, presence of photovoltaic panel systems, and taking steps to improve the indoor comfort quality of climatic parameters reflect the value of media facades in terms of sustainability (Abdou et al, 2017). In addition, in line with the principles of sustainability, the integration of technological advances into building life cycle phases has gained importance with the drive to overcome climate change and achieve the goals of reducing critical global energy consumption.…”
Section: Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, 18% (e.g., [132][133][134][135][136][137][138][139][140][141][142][143][144]) were exclusively male, while 6% (e.g., [94,[145][146][147][148]) were solely femalefocused. The remaining majority (e.g., [37,149,150]) carried out research involving both genders. We believe that studies with a large participant base-exceeding 100, for example-should ideally incorporate both genders, unless the research requires otherwise.…”
Section: Evaluation Of Human Productivitymentioning
confidence: 99%